RF-to-DC converter circuit integrated with antenna design of 2.45 GHZ and 5 GHZ wi-fi energy-harvesting system for ultra-low power applications - Ismail, Nuraiza (2024)
Recent ambient-energy-harvesting technology advances low-power electronic devices in a green and self-sustaining environment. This technology exploits sun, heat, vibration, thermal, and radio-frequency energies. Due to its accessibility and easy scavenging, radio-frequency (RF) energy harvesting is the most prominent one compared to other sources. Nonetheless, the received power strength from naturally ambient RF signals is relatively low in many environments. To address this challenge, researchers have developed more efficient RF-energy-harvesting systems to capture and convert small amounts of the RF energy into a DC power for ultra-low applications. This includes designing and optimising a frequency range of antennas with enhanced harvesting efficiency, with the characteristics of capturing a wider range of RF signals. Various rectification techniques have also been explored to improve conversion efficiency and RF-input power extraction. However, many studies have harvested energy with power levels around -30 dBm, covering only some ambient RF energy since Wi-Fi signals might exceed -50 dBm. Thus, developing a new converter circuit, integrated with the antenna that could scavenge even the small amounts of the ambient RF energy, would be significant for the RF-energy-harvesting system. On top of that, with the intention of minimising overall manufacturing and assembly costs, a novel microstrip rectangular patch antenna, integrated with a non-complex converter circuit design, is presented in this study. Since the RF-harvesting system focuses on harvesting the RF power from the ISM Wi-Fi bands of 2.45 GHz and 5 GHz, a harvester antenna operating a broad ambient signal spectrum and covering both frequency bands with an omnidirectional radiation pattern and a minimum gain of 3 dBi, has been designed. It consists of a rectangular patch with a rectangular slot positioned in the centre, and the upper rectangular patch serves as a parasitic element. The designed antenna has undergone an evolutionary design process with a parametric analysis of the co-planar waveguide position, rectangular slot, and parasitic element. The antenna structure has been optimised until both targeted Wi-Fi frequency bands have been met and fulfilled the requirements for a good performance in terms of reflection coefficient, impedance matching, radiation pattern, and gain. The optimisation antenna has then been connected to the converter circuit to examine the signal characteristics of the harvesting system before further fabrication.